Prospect and Challenges of International Law in ASEAN and in Indonesia ASEAN Charter Aftermath: International Treaty Perspective - Eddy Pratomo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
After the establishment of ASEAN charter, the agenda to which ASEAN countries shall address is that its implementation urgently requires a strong political will and the sufficient supporting framework. For Indonesia, the prospect and challenge for the implementation of this charter is mostlu in the form of the reformation of the law pertinent to the law of international organization. From international perspective, the position of Indonesia as the hosts of the ASEAN headquarter may significantly affect the development of international law, especially on the law of the international organization.Keywords: International Law, ASEAN Charter, ASEAN agreement.